Pulmonary Arteriovenous Fistulae After Fontan Operation: Incidence, Clinical Characteristics, and Impact on All-Cause Mortality - Ohuchi, Hideo; Mori, Aki; Nakai, Michikazu; Fujimoto, Kazuto; Iwasa, Toru; Sakaguchi, Heima; Kurosaki, Kenichi; Shiraishi, Isao (Frontiers in Pediatrics, 2022)
Background The Fontan operation is a surgical procedure used in children with univentricular hearts. Pulmonary arteriovenous fistulae (PAVF) is a major complication after a Fontan operation. However, the incidence and related clinical pathophysiology of PAVF remain unclear. Purpose This study aimed to clarify the incidence of PAVF, its clinical characteristics, and its influence on all-cause mortality. Methods and Results We serially assessed the presence of PAVF using pulmonary artery angiography and/or contrast echocardiography during catheterization in 391 consecutive patients who underwent the Fontan procedure and compared the results with the Fontan pathophysiology and all-cause mortality. PAVF developed in 36 patients (9.2%), including 30 diffuse- and six discrete-PAVF types. The PAVF-free rates at 1, 5, 10, 15, 20, and ≥25 years after Fontan operation were 97, 96, 93, 88, 87, and 83%, respectively. The mean arterial blood oxygen saturation (SaO2) in patients with diffuse PAVF at each corresponding postoperative stage were 90, 91, 91, 91, 89, and 88%, respectively, indicating lower SaO2 levels than those in patients without PAVF (all p < 0.01). However, there was no difference in the SaO2 levels between patients with discrete PAVF and those without PAVF. During a median follow-up period of 2.9 years after the last catheterization, 31 patients, including 12 patients with PAVF, died. Patients with PAVF, especially those with diffuse PAVF, had a higher mortality rate (p = 0.01) than those without PAVF (hazard ratio: 3.6, 95% confidence interval: 1.6–7.8, p = 0.0026). Conclusion Patients who underwent Fontan surgery had an increased incidence of PAVF as they aged. Discrete PAVF did not influence SaO2 or mortality, whereas the presence of diffuse PAVF caused hypoxia and was associated with all-cause mortality.